Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.
Customized for You
we will pick new questions that match your level based on your Timer History
Track Your Progress
every week, we’ll send you an estimated GMAT score based on your performance
Practice Pays
we will pick new questions that match your level based on your Timer History
Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.
Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:
Christina scored 760 by having clear (ability) milestones and a trackable plan to achieve the same. Attend this webinar to learn how to build trackable milestones that leverage your strengths to help you get to your target GMAT score.
(1) e+d = -12 => d = -12-e, however as we don't know anything about e, it could be 1 (thus d=-13) or -13 (thus d=1) = insufficient
(2) e-d < -12 => d > 12+e, again e can be anything => insufficient
(1) + (2) from 1: e=-12-d from 2: e<-12+d together: -12-d < -12+d => -d < +d
this is only true if d is positive.
Therefore: Answer is C
However that's not the text books answer explanation, so I thought I'd ask you guys for your opinion and if there are any flaws in the answer that I overlooked.
(1) e+d = -12 => d = -12-e, however as we don't know anything about e, it could be 1 (thus d=-13) or -13 (thus d=1) = insufficient
(2) e-d < -12 => d > 12+e, again e can be anything => insufficient
(1) + (2) from 1: e=-12-d from 2: e<-12+d together: -12-d < -12+d => -d < +d
this is only true if d is positive.
Therefore: Answer is C
However that's not the text books answer explanation, so I thought I'd ask you guys for your opinion and if there are any flaws in the answer that I overlooked.
Is d negative?
(1) e + d = -12. d can be negative as well as non-negative. For example, consider d=0 and e=-12 and d=-1 and e=-11. Not sufficient.
(2) e – d < -12. d can be negative as well as non-negative. For example, consider d=0 and e=-13 and d=-1 and e=-14. Not sufficient.
(1)+(2) From (1) we have that e = -12 - d, thus from (2) (-12 - d) - d < -12 --> -2d<0 --> d>0. Sufficient.
Re: Is d negative? (1) e + d = -12 (2) e – d < -12
[#permalink]
Show Tags
02 Jul 2015, 09:31
jumli wrote:
Is d negative?
(1) e + d = -12
(2) e – d < -12
Question : Is d < 0?
Statement 1:e + d = -12
@e=2, d=-14 We observe that d may be negative @e=-14, d=2 We observe that d may be Positive
NOT SUFFICIENT
Statement 2: e - d < -12
@e=-15, d=1, e-d = -16 i.e. Less than -12 We observe that d may be Positive @e=-15, d=-2, e-d = -13 i.e. Less than -12 We observe that d may be Negative
NOT SUFFICIENT
Combining the Two statements
e = -12-d and e - d < -12 i.e. (-12-d)- d < -12 i.e. (-12-2d) < -12 i.e. 2d > 0 i.e. d is positive
SUFFICIENT
Answer: option C _________________
Prosper!!! GMATinsight Bhoopendra Singh and Dr.Sushma Jha e-mail: info@GMATinsight.com I Call us : +91-9999687183 / 9891333772 Online One-on-One Skype based classes and Classroom Coaching in South and West Delhi http://www.GMATinsight.com/testimonials.html
Re: Is d negative? (1) e + d = -12 (2) e – d < -12
[#permalink]
Show Tags
16 May 2017, 22:25
Is d negative? (1) e + d = -12 (2) e – d < -12
Ans: From (1), e + d = -12, we can't tell if d is +ve or -ve ( if positive , e is -ve and more in magnitude than d by 12) From (2), e – d < -12 too, we can't tell. Hence , we put (1) into (2), => Putting e= -12 - d => (-12-d) - d < -12 => -12 - 2d < -12 => d > 0
Hence, statements 1 and 2 together are sufficient to answer the question but not alone.
Re: Is d negative? (1) e + d = -12 (2) e – d < -12
[#permalink]
Show Tags
26 May 2018, 07:32
Top Contributor
jumli wrote:
Is d negative?
(1) e + d = -12
(2) e – d < -12
Target question:Is d negative?
Statement 1: e + d = -12 Let's TEST some values. There are several values of e and d that satisfy statement 1. Here are two: Case a: d = -6 and e = -6. Notice that e + d = (-6) + (-6) = -12. In this case, the answer to the target question is YES, d IS negative Case b: d = 1 and e = -13. Notice that e + d = (-13) + 1 = -12. In this case, the answer to the target question is NO, d is NOT negative Since we cannot answer the target question with certainty, statement 1 is NOT SUFFICIENT
Statement 2: e – d < -12 There are several values of e and d that satisfy statement 2. Here are two: Case a: d = 13 and e = 0. Notice that e - d = 0 - 13 = -13, and -13 < -12. In this case, the answer to the target question is NO, d is NOT negative Case b: d = -5 and e = -20. Notice that e - d = -20 - (-5) = -15, and -15 < -12. In this case, the answer to the target question is YES, d IS negative Since we cannot answer the target question with certainty, statement 2 is NOT SUFFICIENT
Statements 1 and 2 combined Statement 1 tells us that e + d = -12 Statement 2 tells us that e – d < -12 If e + d = -12, then e = -12 - d Now take e – d < -12 and replace e with -12 - d to get: (-12 - d) – d < -12 Simplify: -12 - 2d < -12 Add 12 to both sides: -2d < 0 Divide both sides by -2 to get: d > 0[since we divided by a NEGATIVE value, we REVERSED the direction of the inequality symbol] So, the answer to the target question is NO, d is NOT negative Since we can answer the target question with certainty, the combined statements are SUFFICIENT
Re: Is d negative? (1) e + d = -12 (2) e – d < -12
[#permalink]
Show Tags
27 Jun 2018, 10:27
This is a Yes/No question.
Since number testing is quick, it is advisable to to quickly test some scenarios:-
Attachment:
2018-06-27_23-48-51.jpg [ 184.98 KiB | Viewed 2240 times ]
We have seen above that Statement 1 & 2 are not sufficient by own. We are down to C vs E
Hence we combine the two statements. Scenario 1 satisfies the conditions but Scenario 2 does not satisfy the conditions. We need to analyse this further. We need a concrete proof before we conclude either way.
Since it is given that e + d = -12; therefore e = -12 - d Statement (2) states that e – d < -12 therefore substitute e = (-12 - d) to get: (-12 - d) – d < -12 Simplification implies that d > 0 or we get a definite "No" to the question "Is d negative?". Hence for both the equations to hold together d have to be positive therefore (C) is sufficient.
_________________
________________ Manish
"Only I can change my life. No one can do it for me"
Re: Is d negative? (1) e + d = -12 (2) e – d < -12
[#permalink]
Show Tags
01 Feb 2020, 01:56
Hello from the GMAT Club BumpBot!
Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up - doing my job. I think you may find it valuable (esp those replies with Kudos).
Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email.
_________________